Response of Plant-Associated Microbiome to Plant Root Colonization by Exogenous Bacterial Endophyte in Perennial Crops - Yurgel, Svetlana N.; Ajeethan, Nivethika; Smertenko, Andrei (Frontiers in Microbiology, 2022)
The application of bacterial inoculums for improving plant growth and production is an important component of sustainable agriculture. However, the efficiency of perennial crop' inoculums depends on the ability of the introduced endophytes to exert an impact on the host-plant over extended period of time. This impact might be evaluated by the response of plant associate microbiome to the inoculation. In this study we monitored the effect of a single bacterial strain inoculation on the diversity, structure and cooperation in plant-associated microbiome over one-year period. An endophyte (RF67) isolated from Vaccinium angustifolium (wild blueberry) roots and annotated as Rhizobium was used for inoculation of 1 year-old Lonicera caerulea (Haskap) plants. A significant level of bacterial community perturbation was detected in plant roots after 3 months post-inoculation. About 23% of root-associated community variation was correlated with application of the inoculant, which was accompanied by an increased cooperation between taxa belonging to Proteobacteria and Actinobacteriota phyla and decreased cooperation between Firmicutes in plant roots. Additionally a decrease in bacterial Shannon diversity and an increase in the relative abundances of Rhizobiaceae and Enterobacteriaceae were detected in the roots of inoculated plants relative to the non-inoculated control. A strong effect of the inoculation on the bacterial cooperation was also detected after one year of plant field growth, while no differences in bacterial community composition as well as alpha- and beta- diversities were detected between bacterial communities from inoculated and non-inoculated roots. These findings suggest that while exogenous endophytes might have a short-term effect on the root microbiome structure and composition, they can boost cooperation between plant-growth promoting endophytes, which can exist for the extended period of time providing the host-plant with long-lasting beneficial effects.